A phase 1/2 comparative vaccine trial of the safety and immunogenicity of a CRF01_AE (subtype E) candidate vaccine: ALVAC-HIV (vCP1521) prime with oligomeric gp160 (92TH023/LAI-DID) or bivalent gp120 (CM235/SF2) boost - Prasert Thongcharoen (2018)
BACKGROUND: The development of an effective HIV-1 vaccine is critical to control the pandemic. A prime-boost HIV-1 vaccine trial assessing safety and immunogenicity was conducted in Thailand as part of an evaluation of candidate regimens for a phase 3 efficacy trial. METHODS: ALVAC-HIV (vCP1521), expressing circulating recombinant form 01_AE (CRF01_AE) gp120/subtype B LAI and subtype B Gag/Protease boosted with recombinant envelope oligomeric CRF01_AE gp160 (ogp160) or bivalent CRF01_AE/subtype B gp120 CM235/SF2, was evaluated in a phase 1/II trial of 130 HIV-negative Thai adults. RESULTS: One hundred forty volunteers were enrolled, and 130 completed all safety and immunogenicity visits. Reactogenicity was common but generally mild, and there was no significant difference in the adverse event rate between vaccine and placebo recipients (P = 0.26). There were 7 serious adverse events during the follow-up period, none of which were vaccine related. Cumulative HIV-specific, CD8-mediated, cytotoxic T-lymphocyte responses were observed in 11 (25%) of 44 subjects who received ALVAC boosted by bivalent gp120 and in 5 (11%) of 45 subjects who received ALVAC boosted by ogp160, but these differences were not statistically significant compared with those in placebo recipients (P = 0.62 and P = 0.37, respectively). HIV-specific lymphoproliferative responses were detected in 84% of subunit-boosted vaccine recipients and in 10% of placebo recipients. Neutralizing antibody responses to CRF01_AE and subtype B laboratory strains were seen in 95% of ogp160-boosted and 100% of gp120 B/E-boosted vaccinees, respectively. CONCLUSIONS: These 2 different prime-boost regimens seem to be safe and displayed cell-mediated immune responses consistent with those in other trials of canarypox vectors. © 2007 Lippincott Williams & Wilkins, Inc.